THE POTENCY OF Candida albicans PROTEIN EXTRACT AS BIORESEPTOR ON IMMUNOCENCOR TO DIAGNOSE CANDIDIASIS - Masfufatun, Masfufatun; Sudibya, Akhmad; Kumala, Nur (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2014)
So far, diagnosing on candidiasis has still been limited in standard blood culture. The traditional method of this microbiology culture is less sensitive, many patients with candidasis infection have negative blood culture, and need a long time. This case encourage many researchers to use another alternative methode to diagnose. The purpose of this research is to examine the potency of Candida albicans protein extract as bioreseptor on immunocencor to  detect  Candida albicans and its biofilm in the blood of candidiasis patients. The research method which is used is descriptive with the following steps : (1) isolating enzim from the liquid of digestive gland of snail (Achatina fulica); (2) extraction of protein candida albicans  through  enzimatis and mechanic methods and (3) Analyzing the protein extract as bioreseptor through immunodot assay.The research result shows that the snail enzyme has the protein content 1.35 mg/ml and the specific activity 1.96 unit/mg. This snail enzyme can hydrolyze  the cell wall of Candidia albicans  and, with the help oh sonication, produce extract of planktonic extracel protein (PEP) and biofilm (PEB), extract of planktonic intracell protein (PIP), and biofilm (PIB), with each protein content 1.44; 1.29; 1.29 and 1.21 mg/ml. The characeristic of biofilm intracell protein (PIB) is antigenic on antibody anti-candida (positive control) with giving red spot on immunodot assay. Immunodot assay can distinguish negative control serum (health man) and positive Candidiasis control by using antigen 1 ng/nl and 50nl serum.